Delta mass shift as a thermometer of kinetic decoupling in Au + Au reactions at 1.23 AGeV. (29th August 2019) - Reichert, Tom; Hillmann, Paula; Limphirat, Ayut; Herold, Christoph; Bleicher, Marcus
Abstract: The HADES experiment at GSI will soon provide data on the production and properties of Δ(1232) baryons from Au + Au reactions at 1.23 AGeV. Using the Ultra Relativistic Quantum Molecular Dynamics model, we predict the yield and spectra of Δ(1232) resonances. In addition we show that one expects to observe a mass shift of the Δ(1232) resonance on the order of 50 MeV in the reconstructable Δ(1232) mass distribution. This mass shift can be understood in terms of late stage Δ(1232) formation with limited kinetic energy. We show how the mass shift can be used to constrain the kinetic decoupling temperature of the system.